2016
DOI: 10.4103/2251-9572.218745
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual disturbances in women with congenital heart diseases

Abstract: Background: Women with congenital heart disease (CHD) may experience menstrual disturbances secondary to hemodynamic instability during the mensturation phase. Objectives: We investigated the menstrual bleeding pattern and its relationship with certain clinical findings in adult women with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Other studies also found later menarche in complex and cyanotic subgroups. 22 , 57 , 58 In women with Fontan circulation, representing those with highest grade of severity, 3 studies found later age at menarche when compared with the general population. 23 , 24 , 25 To our knowledge, the Fontan population is the only CHD subgroup with previous assessment of Tanner stages.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found later menarche in complex and cyanotic subgroups. 22 , 57 , 58 In women with Fontan circulation, representing those with highest grade of severity, 3 studies found later age at menarche when compared with the general population. 23 , 24 , 25 To our knowledge, the Fontan population is the only CHD subgroup with previous assessment of Tanner stages.…”
Section: Discussionmentioning
confidence: 99%